Rooting of mini-cuttings of Sequoia sempervirens using different clones and cultural environments - de Oliveira Pereira, Mariane; Camargo Ângelo, Alessandro; Navroski, Marcio Carlos; Nicoletti, Marcos Felipe; Nascimento, Bruno; Schatz Sá, Alexandra Cristina; de Oliveira, Luciana Magda; Lovatel, Queli Cristina (BOSQUE, 2019)
Sequoia sempervirens is a fast-growing, long-lived tree with pest-resistant wood. The objective of this study was to quantify the adventitious rooting ability of sequoia clones in two environments as well as determining rooting behavior during the evaluation period. Mini-cuttings of five clones grown in a clonal mini-garden were planted for rooting in two different environments: a mini-tunnel and an intermittently fogging greenhouse. Weekly assessments (from 30 to 93 days) of the variables were performed: survival, rooted mini-cuttings and number of roots emitted. Rooting speed varied in relation to the clones, occurring mainly between 50 and 60 days after planting, with the appearance of new roots between 70 and 80 days. The cultivation environment promoted distinct responses in the rooting process, being earlier in the greenhouse environment, although with a higher index in the mini-tunnel at the end of the evaluation. The process of differentiation of mini-cuttings occurs initially with the formation of calluses, around 15 days, followed by rooting (between 30 and 60 days) and the subsequent appearance of new roots. The rooting of sequoia mini-cuttings can be done in a mini-tunnel, with good indexes for all clones. It is recommended to keep mini-cuttings in this environment for 90 days for good root formation.